Finite Elements and Symmetry (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue of the journal Symmetry contains a collection of papers devoted to the use of symmetry in finite element approximation of partial differential equations. More specifically, applications ranging from mechanical engineering to electromagnetics and fluid dynamics are considered. Both theoretical and computational aspects are considered. The contributions were selected to ensure the widest variety of themes. In particular, we wanted to include both theoretical papers (well posedness, stability) and numerical computations.